EFFECTS OF WHOLE-BODY ACUPOINT CATGUT EMBEDDING, ELECTROACUPUNCTURE, AND MASSAGE-ACUPRESSURE ON PAIN RELIEF AND LUMBAR SPINE RANGE OF MOTION IN PATIENTS WITH LUMBAR-SCIATIC SYNDROME DUE TO LUMBAR SPONDYLOSIS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the analgesic effects and improvement in lumbar spine range of motion of whole-body acupoint catgut embedding combined with electroacupuncture and acupressure in patients with lumbosciatica syndrome caused by degenerative spinal disease.Subjects: A total of 60 patients diagnosed with lumbosciatica syndrome due to degenerative spinal disease were divided into a study group and a control group. All patients were treated at the Department of Traditional Medicine and Rehabilitation, Bao Thang Regional Medical Center, from July 2025 to March 2026.Methods: A prospective, controlled interventional clinical study was conducted, comparing outcomes before and after treatment.Results: After 15 days of treatment, the mean VAS score in the study group decreased from 5.53 ± 0.82 to 1.53 ± 0.63, showing a significantly greater reduction compared to the control group (from 5.37 ± 0.96 to 2.07 ± 0.94) (p < 0.05). Lumbar spine flexibility and range of motion improved more markedly in the study group than in the control group, with statistically significant differences (p < 0.05).Conclusion: Whole-body acupoint catgut embedding combined with electroacupuncture and acupressure is effective in reducing pain and improving lumbar spine range of motion in patients with lumbosciatica syndrome due to degenerative spinal disease.
Keywords: Catgut embedding, electroacupuncture, acupressure, lumbosciatica syndrome, lumbar degenerative spine.